3PC-063 Performance qualification of robotic system for cytotoxic drug preparation in a fully GMP compliant hospital pharmacy. (14th March 2021) - Kytö, E; Suonvieri, P; Moroni, G; Federici, M
Abstract : Background and importance: A robotic system for automated preparation of cytotoxic drugs, such as APOTECAchemo, ensures reduced occupational exposure to toxic substances and aseptic conditions. The most critical operations are performed by a robotic arm; the operator's intervention is limited to loading/unloading materials in a rotating warehouse through an unloading/loading area enclosed within a laminar airflow barrier. In European hospital pharmacies which comply with good manufacturing practice (GMP), the performances of the robot are assessed by GMP qualification to confirm that the technology meets the set quality standards. Aim and objectives: The aim of this study was to evaluate microbiological performances and environmental conditions during fully automated preparation with APOTECAchemo in a grade B cleanroom. Material and methods: Effectiveness of laminar airflow retention was checked by potassium iodide (KI) discus test in the unloading/loading area of the APOTECAchemo robot. Aseptic preparation of cytotoxic drugs was evaluated with media fill simulation tests on three consecutive days. In total, 240 products (180 infusion bags, 30 syringes, 30 elastomeric pumps) were automatically filled with single/double strength tryptic soy broth in lieu of drug products. Microbiological environmental controls were performed by passive air sampling (settle plates, four locations), surface sampling (contact plates/swabs, 14 locations), and active air sampling (three locations). Samples were taken for each shift. Media fill products were visually inspected for turbidity after 14 days of incubation. The number of colony forming units (CFU) per plate were counted and identified. Results: The results of the KI discus test were far below the acceptance limit, demonstrating the effectiveness of laminar airflow in preventing the escape of particles from the internal areas of the robot. None of 240 media fills showed turbidity after incubation, thereby indicating no contamination with microorganisms. The working area met the grade A limit (0 CFU/sample). In the warehouse, 1 CFU was found in two samples (mean 0.2 CFU/contact plate, 0.1 CFU/settle plate). Microbial contamination was slightly higher in the loading area (mean 0.3 CFU/contact plate, 0.8 CFU/settle plate). Most of the CFUs were identified as skin related microorganisms, such as Staphylococcus epidermidis and Staphylococcus hominis . Conclusion and relevance: Extensive media fill tests and environmental monitoring during automated preparation with the robot revealed well controlled aseptic procedures and adequate sterility levels, thereby complying with the quality standard set by the hospital pharmacy. References and/or acknowledgements: Conflict of interest: No conflict of interest